PENGARUH KINERJA MAKROEKONOMI TERHADAP DANA PIHAK KETIGA BANK SYARIAH INDONESIA - Ansheila Yunian Saragih; Lavlimattria Esya (Media Ekonomi, 2016)
This study Aimed to analyze the influence of GDP, SBIS and inflation on third-party funds (DPK), in the short term and long term in the period quarterely 2008: 1 until 2014: 4. The variables used are third party funds (DPK), Gross Domestic Product (GDP), inflation, and Bank Indonesia Certificates Sharia (SBIS). Mmethodology used is a method of Error Correction Model (ECM). Before the test of Error Correction Model (ECM), the models must pass the prerequisite test unit root, integration and Co integration. The results showed the models Prerequisites Error Correction Model (ECM) can be used and passed the prerequisite test. The results using methods Error Correction Model (ECM), it was found that the variable inflation does not significantly influence the Third Party Funds (TPF) in the long term. While in the short term inflation is a significant variable to the Third Party Fund (DPK).